2021
DOI: 10.3390/en15010212
|View full text |Cite
|
Sign up to set email alerts
|

Improving Detection of False Data Injection Attacks Using Machine Learning with Feature Selection and Oversampling

Abstract: Critical infrastructures have recently been integrated with digital controls to support intelligent decision making. Although this integration provides various benefits and improvements, it also exposes the system to new cyberattacks. In particular, the injection of false data and commands into communication is one of the most common and fatal cyberattacks in critical infrastructures. Hence, in this paper, we investigate the effectiveness of machine-learning algorithms in detecting False Data Injection Attacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Table 2 and Fig. 3 show the results offered by the HDL-FDIAD model and other existing models on power dataset [19]. The experimental outcomes confirm that the proposed HDL-FDIAD model gained effectual outcomes on both the class labels.…”
Section: Resultsmentioning
confidence: 55%
“…Table 2 and Fig. 3 show the results offered by the HDL-FDIAD model and other existing models on power dataset [19]. The experimental outcomes confirm that the proposed HDL-FDIAD model gained effectual outcomes on both the class labels.…”
Section: Resultsmentioning
confidence: 55%
“…The proposed prepossessing of data and selection of the most promising features improve the performance of the DT model. The authors in [67] used minority oversampling and feature selection to improve the detection of FCIAs on power systems using machine learning. The authors in [68] showed that the performance of various ML models to detect FCIAs is dependent on pre-processing and feature selection.…”
Section: A Artificial Intelligence-based Techniquesmentioning
confidence: 99%
“…As a multi-label classifier, the CNN method was used to evaluate co-occurrence dependency, irrespective of the power flow computations that occur due to possible attacks. Kumar et al [15] examined the efficiency of ML techniques in identifying the FDIC. Specifically, the authors focused on two commonly-employed critical infrastructures, the water treatment plants and the power systems.…”
Section: Literature Reviewmentioning
confidence: 99%